The Effectiveness Of Video And E-Booklet Media In Health Education On Improving The Knowledge Of Pregnant Women About The Pregnancy Danger Signs At Jetis 1 Public Health Center Of Bantul Regency - Yunita Wiwit Widuri; Margono Margono; Yuliantisari Retnaningsih (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Danger signs of pregnancy before causing complications can be detected early independently through learning media such as videos and e-booklets. The purpose of this study was to determine the effectiveness of video and e-booklet media in improving the knowledge of pregnant women about the danger signs of pregnancy Methods: This study was conducted in December 2020-January 2021 at Jetis 1 Public Health Center, Bantul Regency and used the type of quasi-experimental research and pretest-posttest with control group design. The research subjects were pregnant women in the first, second and third trimesters as many as 24 people for each group. Sampling was collected using purposive sampling technique on respondents with the criteria of being willing to follow the research rules, there is no trouble in seeing/speaking/hearing, being capable to read and write. Respondents who resigned during the study, did not complete the questionnaire until the end and worked as health workers were not taken as research respondents. The measuring instrument used is a questionnaire that has been tested for validity and reliability. The data analysis used Wilcoxon test and Mann Whitney test Results: The results of the analysis show that the two media have an effect on increasing the knowledge of pregnant women with p-value 0,000 for videos and p-value 0,000 for e-booklet Conclusion: Video is more effective than e-booklet in improving the knowledge of pregnant women (p-value 0,031). Thus the video made by researchers can be used to provide health education about the danger signs of pregnancy